Necessary and Sufficient Conditions for Oscillations of Neutral Hyperbolic Partial Differential Equations with Delays (Journal of Partial Differential Equations, 2020)
This paper is concerned with the oscillations of neutral hyperbolic partial differential equations with delays. Necessary and sufficient conditions are obtained for the oscillations of all solutions of the equations, and these results are illustrated by some examples.